2020
DOI: 10.1136/bmjebm-2020-111371
|View full text |Cite
|
Sign up to set email alerts
|

Problem with patient decision aids

Abstract: Patient decision aids are evidence-based tools designed to help patients make specific and deliberated choices among healthcare options. Research shows that patient decision aids increase knowledge, accuracy of risk perceptions, alignment of care with patient values and preferences, and patient involvement in decision making. Some patient decision aids can reduce the use of invasive and potentially low-value procedures. On this basis, clinical practice guidelines and international organisations have begun to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…On the other extreme were some physiotherapists, who suggested that Cochrane systematic reviews have underestimated the true harms of surgery. We did not change the evidence presented because it is vital numeric estimates of benefits and harms in decision aids are based on the highest quality available evidence 15 28…”
Section: Discussionmentioning
confidence: 99%
“…On the other extreme were some physiotherapists, who suggested that Cochrane systematic reviews have underestimated the true harms of surgery. We did not change the evidence presented because it is vital numeric estimates of benefits and harms in decision aids are based on the highest quality available evidence 15 28…”
Section: Discussionmentioning
confidence: 99%
“…Another highlight of the research is the limitation of adequately translating evidence from CPG recommendations [ 63 ]. One of these limitations may be that the guidelines for PtDA development may not be sufficient to ensure that developers select the best available evidence and present the evidence appropriately.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, we consider our evidence reviews comprehensive and well documented. On the other hand, we clearly acknowledge the challenges identified by Zadro et al [ 24 ], who states: “If only low-certainty evidence is available this could leave patients more uncertain than before they read the decision aid. … it is important to consider whether sufficient evidence exists to reasonably produce a well-balanced patient decision aid.” Dealing with often low-quality best available evidence resulting from a high-quality review of the evidence was indeed a huge challenge also in this project.…”
Section: Discussionmentioning
confidence: 75%
“…Several recent reviews of published PtDAs suggest a lack of well documented evidence review and summarization processes [ 11 , 12 , 24 ]. In contrast, we consider our evidence reviews comprehensive and well documented.…”
Section: Discussionmentioning
confidence: 99%